Cyberpragmatic Analysis: A Case Study of Responses to the 'Police Officer Killed in Promotion Talks' Incident - Prombut, Tanchanok (Journal of Social Sciences and Humanities Research in Asia, 2025)
This study investigates the cyberpragmatics of verbal irony in Thai online discourse, focusing on netizens' reactions to the death of a police officer during promotion discussions. A dataset of 635 comments, collected from the official Facebook page of the talk show Hon Krasae (September-October 2023), captured immediate public responses, ensuring that reactions reflected spontaneous sentiment rather than retrospective rationalisation. Using a mixed-methods design, both quantitative and qualitative analyses were conducted on the original Thai-language comments, with attention to linguistic and cultural nuances. Content analysis identified eight communicative forms: Ironic Criticism (23.31%), Explicit Criticism (17.64%), Interrogative (15.12%), Ironic Compliments (12.91%), Implicit Sarcasm (10.39%), Third-person Sarcasm (9.76%), Direct Suggestion (8.82%), and Slang/Colloquial Usage (2.05%). Verbal irony often functioned as implicit social critique, exemplified by comments such as "Good people will get rewards for their work. It's a normal thing," which contrasted surface meaning with the reality of rejecting corruption. The findings suggest that irony and sarcasm serve complementary roles: irony provides implicit critique, while sarcasm conveys more overt evaluation. By highlighting these functions, the study enhances media literacy, equipping readers to recognise and interpret irony in online communication and offering deeper insight into its role in Thai digital discourse.